Spotlight on advances in VTE management: CALLISTO and EINSTEIN CHOICE - Bach, Miriam; Bauersachs, Rupert (Thrombosis and Haemostasis, 2016)
Venous thromboembolism (VTE) is associated with numerous complications and high mortality rates. Patients with cancer are at high risk of developing cancer-associated thrombosis (CAT), and VTE recurrence is common. Evidence supporting use of non-vitamin K antagonist (VKA) oral anticoagulants (NOACs) in patients with cancer is lacking – direct comparisons between NOACs and low-molecular-weight heparin (LMWH) are needed, along with patient-reported outcomes. Cancer Associated thrombosis – expLoring soLutions for patients through Treatment and Prevention with RivarOxaban (CALLISTO) is an international research programme exploring the potential of the direct, oral factor Xa inhibitor rivaroxaban for the prevention and treatment of CAT, supplementing existing data from EINSTEIN DVT and EINSTEIN PE. Here, we focus on four CALLISTO studies: A Study to Evaluate the Efficacy and Safety of Rivaroxaban Venous Thromboembolism Prophylaxis in Ambulatory Cancer Participants receiving Chemotherapy (CASSINI), Antico-agulation Therapy in SELECTeD Cancer Patients at Risk of Recurrence of Venous Thromboembolism (SELECT-D), Rivaroxaban in the Treatment of Venous Thromboembolism in Cancer Patients – a Randomized Phase III Study (CONKO-011) and a database analysis. Optimal anticoagulation duration for VTE treatment has always been unclear. Following favourable results for rivaroxaban 20 mg once-daily (Q. D.) for secondary VTE prevention (EINSTEIN EXT), EINSTEIN CHOICE is assessing rivaroxaban safety and (20 mg Q. D. or 10 mg Q. D.) vs acetylsalicylic acid (ASA), and will investigate whether an alternative rivaroxaban dose (10 mg Q. D.) could offer long-term VTE protection. It is anticipated that results from these studies will provide important answers and expand upon current evidence for rivaroxaban in VTE management.
Keywords: Cancer-associated thrombosis; venous thromboembolism; thromboprophylaxis; rivaroxaban